Postural control assessment in students with normal hearing and sensorineural hearing loss - Renato de Souza Melo; Andrea Lemos; Carla Fabiana da Silva Toscano Macky; Maria Cristina Falcão Raposo; Karla Mônica Ferraz (Brazilian Journal of Otorhinolaryngology, 2015)
INTRODUCTION: Children with sensorineural hearing loss can present with instabilities in postural control, possibly as a consequence of hypoactivity of their vestibular system due to internal ear injury.OBJECTIVE: To assess postural control stability in students with normal hearing (i.e., listeners) and with sensorineural hearing loss, and to compare data between groups, considering gender and age.METHODS: This cross-sectional study evaluated the postural control of 96 students, 48 listeners and 48 with sensorineural hearing loss, aged between 7 and 18 years, of both genders, through the Balance Error Scoring Systems scale. This tool assesses postural control in two sensory conditions: stable surface and unstable surface. For statistical data analysis between groups, the Wilcoxon test for paired samples was used.RESULTS: Students with hearing loss showed more instability in postural control than those with normal hearing, with significant differences between groups (stable surface, unstable surface) (p < 0.001).CONCLUSIONS: Students with sensorineural hearing loss showed greater instability in the postural control compared to normal hearing students of the same gender and age.